Conversational Writing - A Multidimensional Study of Synchronous and Supersynchronous Computer-Mediated Communication - Jonsson, Ewa (English Corpus Linguistics, 2015)
The author analyses computer chat as a form of communication. While some forms of computer-mediated communication (CMC) deviate only marginally from traditional writing, computer chat is popularly considered to be written conversation and the most "oral" form of written CMC. This book systematically explores the varying degrees of conversationality ("orality") in CMC, focusing in particular on a corpus of computer chat (synchronous and supersynchronous CMC) compiled by the author. The book employs Douglas Biber's multidimensional methodology and situates the chats relative to a range of spoken and written genres on his dimensions of linguistic variation. The study fills a gap both in CMC linguistics as regards a systematic variationist approach to computer chat genres, and in variationist linguistics as regards a description of conversational writing.